1998
DOI: 10.1161/01.str.29.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Other Risk Factors for Silent Cerebral Infarction in the General Population

Abstract: Background and Purpose-Silent cerebral infarctions (SCIs) have a prevalence between 10% and 40% in the transient ischemic attack population and have been associated with increased mortality and morbidity; however, little is known about the prevalence and risk factors for SCI in the general population. This report focuses on the role of cigarette smoking and other risk factors for SCI in the general population. Methods-MRI scans were performed on 1737 participants selected from the general population as part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
173
6
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(199 citation statements)
references
References 41 publications
14
173
6
6
Order By: Relevance
“…We found a prevalence of SBI of 11.3% in community-dwelling subjects with a mean age of 64.5 years. This is comparable with two prior studies, the Atherosclerosis Risk in Community (ARIC) Study 18 and the Framingham Heart Study 11 (prevalence and mean age: 11%, 63 years and 10.7%, 61 years, respectively). A Japanese brain check-up study, among participants who received MRI at their own expense, reported a similar prevalence of 10.6%.…”
Section: Discussionsupporting
confidence: 88%
“…We found a prevalence of SBI of 11.3% in community-dwelling subjects with a mean age of 64.5 years. This is comparable with two prior studies, the Atherosclerosis Risk in Community (ARIC) Study 18 and the Framingham Heart Study 11 (prevalence and mean age: 11%, 63 years and 10.7%, 61 years, respectively). A Japanese brain check-up study, among participants who received MRI at their own expense, reported a similar prevalence of 10.6%.…”
Section: Discussionsupporting
confidence: 88%
“…[9][10][11][12][136][137][138] Stroke risk decreases substantially within 5 years in those who quit smoking compared with continuing smokers. 10,12 In the Framingham Heart Study, the relative risk of carotid artery stenosis >25% was approximately 1.1 for every 10-mg/dL increase in total cholesterol.…”
Section: Risk Factor Managementmentioning
confidence: 99%
“…6,7 In Japanese patients, the risk of clinical stroke was significantly higher in subjects with SBI (around a threefold increase) than in those without SBI; 8 therefore, the presence of SBI could tell us of the need for an interventional approach to prevent the onset of severe cerebral ischemia. The risk factors for SBI, such as metabolic syndrome, 9 hypertension 10 and smoking, 6 have been reported previously. Interestingly, among older Japanese subjects, white-coat hypertensives do not show an increase in the prevalence of SBI compared with normotensives.…”
mentioning
confidence: 99%
“…5 The incidence of SBI in the general population is relatively high; overall, its prevalence is around 11%. 6 The presence of SBI may allow us to clinically predict overt stroke in the future. 6,7 In Japanese patients, the risk of clinical stroke was significantly higher in subjects with SBI (around a threefold increase) than in those without SBI; 8 therefore, the presence of SBI could tell us of the need for an interventional approach to prevent the onset of severe cerebral ischemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation